Potentials of Gene Therapy for Diabetic Retinopathy: The Use of Nucleic Acid Constructs Containing a TXNIP Promoter - Lalit, PS (Open Access J Ophthalmol, 2018)
Diabetic retinopathy (DR) is considered as a chronic eye disease leading to blindness. DR is associated with hyperglycemia-induced oxidative stress, chronic low-grade inflammation and premature cell death. DR affects retinal capillaries, neuroretina and the retinal pigment epithelium. Recently, the thioredoxin-interacting protein TXNIP has been shown as a pro-oxidative stress, pro-inflammatory and pro-apoptotic protein, highly induced by diabetes and high glucose in all cells examined including the retina. TXNIP’s actions involve binding to and inhibition of anti-oxidant and thiol-reducing capacities of thioredoxins (Trx) causing cellular oxidative stress and apoptosis. Trx1 is found in the cytosol and nucleus while Trx2 is the mitochondrial isoform. Several studies provided evidence that knockdown of TXNIP by siRNA or chemical blockade ameliorates early abnormalities of DR including endothelial dysfunction, pericyte apoptosis, Müller cell gliosis and neurodegeneration. Therefore, TXNIP is considered a potential target for preventing or slowing down the progression of DR. We recently proposed that nucleic acid constructs containing a proximal TXNIP promoter linked to a redox gene or shRNA that reduces oxidative stress and inflammation may be used to treat DR. The TXNIP promoter is sensitive to hyperglycemia therefore can drive expression of the linked gene or shRNA under high glucose environment such as seen in diabetes while remaining unresponsive at physiological glucose levels. Such a TXNIP-promoter linked gene or shRNA construct can be delivered to the retina by using adeno-associated viral vectors including AAV2 and AAV2/8 or an appropriate carrier via the intravitreal or sub retinal delivery for long-term gene therapies in DR.